BARBARA KOCÓWNA AS REYMONT’S BIOGRAPHER - Samborska-Kukuć, Dorota (Prace Polonistyczne, 2022)
Barbara Kocówna’s contribution to the study of the life and works of W.S. Reymont is rather remarkable. She wrote an important monograph about the author of The Peasants and published: large and small editions of his correspondence which she read from the manuscripts, an anthology of texts about Reymont, a chronological record of Reymont’s life, and interpretations of his works (especially of The Promised Land). Kocówna used verified sources to challenge myths about the writer and expressed her opinions and judgments in a very cautious way. Her aim was to gather and systematize reliable information and offer fair judgement. Over time, her research, free from ideological entanglements, did not lose its relevance. In fact, when studying Reymont, it is hard not to refer to Kocówna’s works. They have served as the foundation for the studies of Reymont’s biographical research and writing, although it should be noted that many of her post-1990 findings after come from the unpublished texts written by Witold Kotowski, which Kocówna used in her works.